Pertanggung Jawaban Pidana Pelaku Tawuran Antar Pelajar (Lex Jurnalica, 2012)
Students who are physically and psychologically is still a young free spirit who often obey the rule, they actually also a figure that is also easily influenced by the lifestyle of the surrounding community. Due to the unstable psychiatric conditions, students are still impressionable adolescent aggressive behavior. They tend to take shortcuts and do not want to worry about the negative impact. Aggressive behavior in passing any adverse behavior or cause casualties on the part of others can be termed as aggressive behavior. The term juvenile delinquency refers to a range of behaviors, ranging from behavior that is socially unacceptable (such as school overreacted), violations (such as running away from home), to criminal acts (such as stealing) . Issues that will be addressed in this study is How punishment applied in the case of student brawls? The purpose of this study was to determine how the punishment is applied in the case of student brawls. In preparing this study the authors use the method of normative legal research, this paper is arrange in descriptive prespectif. The conclusion that the authors get from this study is that the students themselves need to fill their spare time with something more useful, such as following the course of events, exercising, following extracurricular activities, and others. Family environment can also prevention brawl. Parents are a good example by not showing aggressive behavior, such as hitting, insulting and mocking. In addition, the role of school organizations also have a role in addressing the prevention of brawls, including a well organized education curriculum is able to develop in a balanced three potentials, namely thinking, estetika, and belief in God.Keywords: responsibility, criminal, fighting between student